Cytotoxic Activity of Cardiospermum halicacabum L. against Oral Cancer Cell Lines.-SCC25 - Sivakali, Vaishnavi; Thangavelu, Lakshmi (Asian Journal of Biological and Life Sciences, 2020)
Aim:To evaluate the Cytotoxic activity ofCardiospermum halicacabumL. against oral cancer cell lines (SCC25).Method:Oral cancer cells were plated in 96 well flat bottom tissue culture plates at a density of approximately 1.2 × 104 cells/well and allowed to attach overnight at 37oC. The medium was then discarded and cells were incubated with different concentrations of the samples (25, 50, 75, 100 and 125 μg/ml) for 24 hours. After the incubation, medium was discarded and 100 μl fresh medium was added with 10 μl of MTT (5mg/ml). After 4 hrs, the medium was discarded and 100 μl of DMSO was added to dissolve the Formosan crystals. Then, the absorbance was read at 570 nm in a microtitre plate reader. Cyclophosphamide was used as a positive control for the Cancer cell lines. Medium along with cells (untreated) serves as a control.Results:Our present study showed the cytotoxicity levels ofCardiospermum halicacabumL. in conjunction with a positive control Cyclophosphamide at different concentration (25 μg/mL,50μg/mL,75 μg/mL, 100 μg/mL, 125 μg/mL). Cyclophosphamide is chosen as positive control as it’s known for its cyctotoxicity ability in cancer cell lines. The cyctoxicity level seems to increase with increase in concentration of the compound. While comparing test compound with the positive control the cyctotoxicity levels of the test compound were as less efficient as the cyclophosphamide but within the compound concentrations had good cytotoxicity capacity.Conclusion:Hence furthermore investigations with higher concentrations and using this product with other compounds as adjuvant can give a better result.
Keywords: Cancer cell lines; Cardiospermum halicacabum L; cyclophospahmide; cytotoxicity; Oral cancer